Analisis Potensi Gas Rumah Kaca dari Sektor Energi di Universitas Singaperbangsa Karawang - Rani, Andina Puspita; Adzillah, Wilma Nurrul; sadidan, Ikhwanussafa (Universitas Tanjungpura, 2026)
Climate change is an increasingly pressing global issue, and greenhouse gas emissions are among its main drivers. Greenhouse Gases are gases found in the atmosphere that absorb and re-emit infrared radiation from Earth, causing an increase in Earth's surface temperature. The researcher aims to calculate and analyze CO2 emissions resulting from the identification of transportation activities on campus 1 of Singaperbangsa University, Karawang. The researcher uses direct observation. The primary data in this study are the numbers of vehicles and electronic devices, such as lights and air conditioners. The use of electricity results in a potential Greenhouse Gas emission of 19,982 kg CO2eq at Singaperbangsa University, Karawang, representing 56% of the total. Motorized vehicles have a potential greenhouse gas emission of 15,807 kgCO2eq at Singaperbangsa University, Karawang, accounting for 44% of the total. The total potential Greenhouse Gas emissions from electricity use and motorized vehicles at Singaperbangsa University, Karawang, amount to 35,789 kg CO2eq.